Effects of Achillea tenuifolia Lam. hydro-alcoholic extract on anxiety-like behavior and reproductive parameters in rat model of chronic restraint stress. (November 2021) - Bagheri, Y; Fathi, E; Maghoul, A; Moshtagh, S; Mokhtari, K; Abdollahpour, A; Montazersaheb, S; Bagheri, A
Introduction: Achillea tenuifolia Lam ( AT ) has several biological activities and medicinal properties. In this study, we elucidated the impact of the AT on anxiety-related behaviors, reproductive parameters, antioxidant capacity in male rats subjected to chronic restraint stress (CRS). Methods: 35 Wistar rats were divided into five groups: control, CRS-control (received normal saline) and three CRS-treated groups received AT extract (100, 150, and 200 mg/kg body weight) for 21 consequences days. To induce CRS rats, the rats were immobilized for 21 days and received the extract orally. On the last day of treatment, anxiety-related behaviors were assessed through the sucrose preference test (SPT) as well as elevated plus maze (EPM) tests. Corticosterone, luteinizing hormone (LH), and follicle-stimulating hormone (FSH), testosterone levels were evaluated to determine reproductive capacity. Sperm parameters including the total count, motility, and viability were also analyzed. Weight of body, testis and seminal vesicles was measured as well. Results: The findings revealed that 100, 150, and 200 mg/kg of AT extract had anxiolytic effects in CRS rats, as confirmed by the EPM test and SPT. In addition, AT extract could improve fertile capacity and sperm quality to varying degrees. The level of corticosterone had decreased, whereas the level of LH, FSH and testosterone had increased in CRS-treated rats. Moreover, the reduced level of MDA coincided with an increased rate of antioxidant capacity. Our findings suggest that AT extract could alleviate stress-induced dysfunctions. Conclusion: Overall, these observations would infer that AT extract could improve fertility capacity and behavioral impairment in the stress conditions. Graphical abstract: Assumption pathway describing the probability underlying mechanism of CRS-induced anxiety and reproductive toxicity and protective effect of AT.